Developing countries and agricultural negotiations : much more is needed - Diaz-Bonilla, Eugenio (2003)
Posits that although the European Union's Common Agricultural Policy (CAP) reform may put pressure on the United States to revise its own increasingly domestic support measures, overall those reforms are not enough.